Assessing SAARC’s Diplomatic Performance: Crisis Management, Regional Cooperation, and Institutional Challenges in South Asia - Shahbaz, Khadija; Muzaffar, Muhammad (Annals of Human and Social Sciences, 2025)
This qualitative paper analyses the performance of SAARC diplomacy in view of regional and global upheavals, with special reference to its ability to manage political disputes, economic difficulties and social mistrust among the members. Based on content analysis of official SAARC documents, elite interviews, and academic literature, the study investigates how SAARC has managed diplomatic crises and advanced regional cooperation in the face of enduring obstacles, including bilateral disputes, geopolitical competition, and developmental discrepancies. The results indicate that while SAARC’s institutional mechanisms provide a forum for dialogue and the consensus building process, the organization’s diplomatic initiatives have frequently been hampered by political distrust and absence of monitoring mechanisms. At the same time, it also points out a few instances in which SAARC had contributed to confidence-building measures as well as conflict resolution processes and joint economic projects, which demonstrates its potential role as a regional stabilizer. The study also highlights the need for SAARC to strengthen its institutional infrastructure, cultivate more political will in its member countries, and adopt non-exclusive and more pragmatic diplomacy to control upheavals in the region. Finally, another related aspect that the contribution makes towards distilling the complex dynamics of regional diplomacy in South Asia while indicating future directions to reinforce the role of SAARC as an architect of peace, stability, and development.